Peran Orang Tua dalam Pendidikan Agama di Rumah dan Pengaruhnya Terhadap Perilaku Anak di Desa Pemongkong Kecamatan Jerowaru: The Role of Parents in Religious Education at Home and Its Influence on Children's Behavior in Pemongkong Village, Jerowaru District - Sarudin Efendi; Suparlan; Yeni Marisa (Pendidikan Al-Gafari, 2025)
Religious education is a fundamental aspect in shaping a child's character and morals. In this context, parents play a crucial role as their children's first and primary educators. This study aims to examine the role of parents in religious education at home and its influence on children's behavior in Pemongkong Village, Jerowaru District. The background of this research is based on the importance of the family as the first and foremost educational environment in shaping children's religious character. Parents are not only caretakers but also spiritual educators through example, habituation, and supervision. This research employed a quantitative approach with a correlational method. Data were collected through questionnaires, interviews, and observations involving 30 parents and 30 children selected using purposive sampling. Data analysis was conducted using Pearson correlation via SPSS software, supported by qualitative data for deeper interpretation. The results show that the role of parents in religious education is categorized as high, and children’s behavior is generally good. The correlation analysis revealed a positive and significant relationship between the role of parents and children's behavior, with a correlation coefficient of r = 0.701 and a significance level of 0.000 (p < 0.05). These findings are supported by interview and observation data indicating that religious habituation, communication, and parental modeling strongly influence children’s daily attitudes and behaviors. In conclusion, the role of parents in providing religious education at home significantly influences the formation of children's behavior. This study emphasizes the importance of active parental involvement in instilling Islamic values in children from an early age.